2005
DOI: 10.1007/s00421-004-1306-z
|View full text |Cite
|
Sign up to set email alerts
|

Moderate hypoxia does not affect the zone of thermal comfort in humans

Abstract: The zone of thermal comfort was determined during normoxia and hypoxia in 15 healthy normothermic young subjects. Subjects dressed only in shorts/shorts and bikini top donned a water-perfused suit and assumed a supine position on a bench. The ambient temperature was maintained at a mean (SD) of 25.7 (0.3) degrees C. The thermal comfort zone was determined by increasing the temperature of the water perfusing the suit from cool to warm. During the heating process, subjects were instructed to report when their pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 28 publications
(47 reference statements)
4
12
0
Order By: Relevance
“…Moreover, previous findings that neither hypoxia nor inactivity/ unloading per se alter behavioural thermoregulatory responses (Golja and Mekjavic, 2003;Golja et al, 2005;Yogev et al, 2010) are confirmed by the present results, and extended to include that the combination of hypoxia and inactivity/unloading does not affect behavioural thermoregulation. No statistically significant differences were found when observing the separate and combined effects of normobaric hypoxia and/or inactivity/unloading.…”
Section: The Combined and Separate Effect Of Inactivity/unloading Andsupporting
confidence: 90%
See 3 more Smart Citations
“…Moreover, previous findings that neither hypoxia nor inactivity/ unloading per se alter behavioural thermoregulatory responses (Golja and Mekjavic, 2003;Golja et al, 2005;Yogev et al, 2010) are confirmed by the present results, and extended to include that the combination of hypoxia and inactivity/unloading does not affect behavioural thermoregulation. No statistically significant differences were found when observing the separate and combined effects of normobaric hypoxia and/or inactivity/unloading.…”
Section: The Combined and Separate Effect Of Inactivity/unloading Andsupporting
confidence: 90%
“…However, the results reported by Golja and Mekjavic (2003) and Golja et al, (2005) indicate that behavioural temperature regulation does not appear to be compromised by moderate hypoxia. Present results from the HAMB condition confirm previous findings (Golja and Mekjavic, 2003;Golja et al, 2005), and extend them to suggest that neither acute nor prolonged exposure to moderate hypoxia affects behavioural thermoregulation.…”
Section: The Combined and Separate Effect Of Inactivity/unloading Andmentioning
confidence: 74%
See 2 more Smart Citations
“…Given that shivering and sweating are not required for thermal behaviour to be initiated, the present study provides mechanistic insights in support of previous studies that have identified no effect of hypoxia (Golja & Mekjavic, ; Golja et al . ) and bed rest (Yogev et al . ) on thermal behaviour.…”
Section: Discussionmentioning
confidence: 99%